CALVING INTERVAL SAPI PERAH LAKTASI DI BALAI BESAR PEMBIBITAN TERNAK UNGGUL DAN HIJAUAN PAKAN TERNAK (BBPTU-HPT) BATURRADEN PURWOKERTO JAWA TENGAH - Yuli Prasetyo; Madi Hartono; Siswanto . (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The aim of this research are to know calving interval and factor´s at lactation dairy cattle in BBPTU-HPT Baturraden Purwokerto Central Java. This research was conducted on April 29 th -- May 13 th 2014 to on 151 heads lactating dairy cattle. This research used sensus method, data obtained was real data that present and accuread in BBPTU-HPT Baturraden. Analysis data used regression analysis with SPSS (Statistik Packet for Social Science). The result showed that the calving interval at lactating dairy cattle in BBPTU-HPT Baturraden is 14.80 ± 3.36 months. Factor that effect calving interval at lactating dairy cattle in BBPTU-HPT Baturraden from the herds man level are the number of cattle that maintain positively associated with factor value 0.177 and the distance between the cow shed with office that negatively assosiated with factor value 0.243. factor that efect calving interval on dairy cattle at the level of cattle are the age dairy cattle that positively associated with factor value 0,247;, periode lactation that negatively assosiated with factor value 0,287;, mating partus that positively associated with factor value 0,057;, lactating period that positively associated with factor value 0,904;, and dry priod that positively associated with factor value 0,961.